2022
DOI: 10.1093/rap/rkac074
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-based stress reduction to improve depression, pain and high patient global assessment in controlled rheumatoid arthritis

Abstract: Objective To improve distressing patient-reported outcomes (PROs) that persisted in rheumatoid arthritis patients with clinically controlled inflammation (controlled RA). Methods In a pragmatic pilot study, we offered Mindfulness-Based Stress Reduction (MBSR), a group intervention to controlled RA patients who had high (≥16) Centre for Evaluation Studies—Depression (CES-D) scores and/or Patient General Assessment of disease a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Salvador proved that MBSR could improve the psychological distress, general well-being, and fatigue-related quality of life 32 . Gaboury showed that up to 12 months after MBSR, anxiety, depression, emotion-oriented coping, sleep and function significantly improved 33 . Elimimian showed cancer survivors who participated in an 8-week MBSR reported persistent benefits with reduced anxiety, depression, and improved mental health over 24 months of follow-up 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Salvador proved that MBSR could improve the psychological distress, general well-being, and fatigue-related quality of life 32 . Gaboury showed that up to 12 months after MBSR, anxiety, depression, emotion-oriented coping, sleep and function significantly improved 33 . Elimimian showed cancer survivors who participated in an 8-week MBSR reported persistent benefits with reduced anxiety, depression, and improved mental health over 24 months of follow-up 34 .…”
Section: Discussionmentioning
confidence: 99%
“…85 The effects of mindfulness-based stress reduction (MSBR) in RA has been investigated in a pilot study of subjects reporting depressive symptoms and/or high PGA despite controlled disease activity measures. 86 The intervention had a marked and enduring impact on depression, anxiety, sleep quality, emotion-oriented coping and a strong positive impact on function. However, these improvements translated into minor or no changes in other RArelated symptoms such as pain and PGA.…”
Section: Do Neuropsychological Interventions Have a Role In Pain Mana...mentioning
confidence: 99%